Factors that influenced consumer acceptance towards online shopping behaviour among employees in Majlis Perbandaran Hang Tuah Jaya Melaka / Marliany Abdullah - Abdullah, Marliany (Faculty of Business and Management, 2018)
This study is intends to investigate the factors influencing consumer acceptance towards online shopping behaviour among employees in Majlis Perbandaran Hang Tuah Jaya Melaka. Five objectives have been determined in this study. First, to identify whether there is a significant relationship between perceived usefulness and consumer acceptance towards online shopping behaviour. Second, to identify the whether there is a significant relationship between website design quality and consumer acceptance towards online shopping behaviour. Third, to identify whether there is a significant relationship between time saving and consumer acceptance towards online shopping behaviour. Next, to identify whether there is a significant relationship between perceived risk and consumer acceptance towards online shopping behaviour. Lastly, to identify the factor that gives most influence on consumer acceptance towards online shopping behavior.